PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN RUMAH TIPE 42 VILLA ARIMA GARDEN PADA PT. ARIMA KARYA PROPERTY PEKANBARU - Syafrina, Nova; Darsih, Deni Tri (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This study aims to determine the effect of price on consumer decisions in buying a house type 42 Villa Arima Garden at PT Arima Karya Property Pekanbaru. From the results of the SPSS test, the t-count is 3.481 and also basedÂ  on the significance test table, the t-table is 2.022. From the two tests, it can be concludedthattcount(3.481) > t table (2.022). And also the significance level obtained is 0.01 < 0.05. Thus, it can be concluded that the price has a significant effect on consumer decisions in buying a house type 42 Villa Arima Garden at PT Arima Karya Property Pekanbaru. The value of R-square (Coefficient of Determinants) is 0.237.It can be concluded that the amount of price on consumer decisions in buying a house type 42 Villa Arima Garden at PT Arima Karya Property Pekanbaru is 23.70%. The relationship of price to consumer decisions in buying a house type 42 Villa Arima Garden at PT. Arima Karya Property Pekanbaru is negative as evidenced by the regression coefficient (b) of -0.34